Examination of the studies done on the reading understanding skills of primary school students - Aşır Turan (Ömer Gökhan Ulum, 2022)
Reading and reading comprehension skills are an important stage in the educational process of children. Learning skills that begin with birth continue throughout human life. The aim of this study is to examine the studies carried out to improve the reading comprehension skills of primary school students according to certain criteria and to determine the general trend in the field. In the realization of the study, steps were followed according to the descriptive survey model. As a result of the literature review, 51 studies that met the inclusion criteria were examined. The studies included in the research were analyzed using the information form prepared by the researchers. In the study, descriptive content analysis, one of the types of systematic review approach, was used. As a result of the research, it was seen that the studies aimed at improving reading comprehension mostly consisted of master's theses, the sample group was concentrated at the 4th grade level, they were carried out with an experimental research model, the strategies, methods and techniques applied varied, and mostly had a positive effect on the development of reading comprehension skills.